AlphaBrain how a group of iconoclasts are using cognitive science to advance the business of alpha generation - Duneier, Stephen 1967- (Gildan, 2019)
Investing has always been a largely reactive field, but those who dominate it approach decision-making less like a human and more like a machine. AlphaBrain shows you how to get real about investing, with cognitive techniques that lead to smarter, evidence-based decisions.
Online resource; title from title details screen (OverDrive, viewed April 4, 2019)
Keywords: Investments -- Psychological aspects; Self-actualization (Psychology); Investissements; Aspect psychologique; BUSINESS & ECONOMICS; Decision-Making & Problem Solving; Investments; Psychological aspects; Downloadable audio books; Audiobooks; Livres audio